Peran Hukum Perikatan dalam Mendukung Perkembangan Hukum di Indonesia : Peluang dan Hambatan - Lulu Agustiani; Nirma Sri Asyfa; Nova Novian Tika; Reggy Rahadian Taufiqurrahman; Reyna Yuliza Mahmudah (Letterlijk, 2024)
Engagement law has an important role in the development of the Indonesian legal system. As part of civil law, engagement law regulates various types of contractual relationships between individuals and legal entities, including commercial transactions, sales contracts, employment contracts, and various other forms of contracts. The development of contract law in Indonesia was influenced by the Dutch during the colonial period, reflected in the Civil Code which has been in effect since 1848. However, there are various obstacles in enforcing contract law in Indonesia. One of the main obstacles is the existence of different legal systems, such as customary law, Islamic law and national law. The purpose of this article is to analyze the role of engagement law in supporting legal development as well as the opportunities and obstacles faced in implementing engagement law in Indonesia. The research method used is normative juridical. Based on the research results, it can be concluded that Indonesian contract law plays a role in regulating various aspects of people's lives, such as leasing and credit contracts. Engagement law also plays a role in providing legal protection for parties related to contractual activities, resolving disputes that occur between parties in contractual agreements, both through litigation and through non-litigation.  Opportunities for involvement in contract law are very important in supporting legal development in Indonesia. One of the main opportunities is the use of information technology. This provides the opportunity to develop new forms of legal contracts, such as digital contracts and smart contracts. In supporting the development of law in Indonesia, the law of engagement faces various obstacles. One of the main obstacles is limited understanding, lack of competent human resources and limited law enforcement support facilities.